Neodvisnost in nepristranskost mednarodnih sodnikov in arbitrov - Kramberger Mendek, Urška (visokošolska dela, 2022)
Independence and impartiality of international judges and arbiters contributes crucially to the establishment and preservation of rule of law by international courts and arbitrations, as well as to the credibility of the judiciary and public trust in it. International courts and arbitrations occasionally encounter complaints about the independence and impartiality of their individual members. Questions of judicial independence are therefore regulated in the Statutes and rules, which also regulate procedures for disqualification in the event of presumed violations of the principles of impartiality and independence by judges or arbiters. The question of independence and impartiality of international judges and arbiters is also connected to their selection procedures which are completely in the hands of individual countries. National procedures vary greatly between countries and are not necessarily formalized. The process in Slovenia is regulated in detail in the Act on nomination of candidates from the Republic of Slovenia for judges at international courts; some countries have established practices, e.g. selection panels, but there are countries where nominations of candidates are seen as a reward. In Courts where states are not guaranteed a position of a judge (e.g. International Court of Justice, International Criminal Court, International Residual Mechanism for Criminal Tribunals, International Tribunal for the Law of the Sea), national nominations are followed by elections at the international level. Those are accompanied by intensive several-month or even multi-year campaigns, with participation of judicial candidates, who, with the extensive support of their country, lobby for votes of the states and their election. It is therefore necessary to announce the candidacy for a judge very early on to be successful; something that is very difficult due to the rigid regulation in the aforementioned Slovenian Law. At the same time, there is some inconsistency in the application of the law for candidacies into certain bodies as well as a discrepancy regarding the relationship with the National Group at the Permanent Court of Arbitration, which, in accordance with the Statute of the ICJ, is the only one that can nominate judicial candidates for it.
Keywords: arbitraža; arbitri; Disertacije; kršitve; Meddržavno sodišče; Mednarodna sodišča; mednarodni sodniki; Mednarodno pravo; neodvisnost; nepristranskost; volitve